Assessment of Indonesia’s Mineral Value-Added Policy: A Literature Review and Future Research Agenda - Andri Budhiman Firmanto; Dermawan Wibisono; Manahan Parlindungan Saragih Siallagan; Mohammad Zaki Mubarok (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2024)
This study addresses a gap in Indonesia’s mineral-downstream policy research by identifying the optimal policy scenario for enhancing the added value of primary metal mineral commodities. This research examines competitive and comparative advantages and economic impacts using system dynamics modeling. Initially, qualitative interviews are conducted to identify elements affecting domestic refining facilities’ growth, followed by quantitative surveys and the Analytic Hierarchy Process (AHP) to prioritize factors fostering these advantages. Findings suggest that developing existing theories to fit Indonesia’s specific context is crucial, and focus group discussions with key mining company decision makers are recommended to develop relevant indices. This method evaluates policy options to determine those offering the most significant economic advantage for each mineral type by analyzing unique characteristics and mapping them to suitable policies. Integrating competitive and comparative advantages into the mineral-added value policy context maximizes economic returns and provides practical recommendations for policymakers, addressing a critical gap in the literature.